Effect of Repeated Intravenous Amantadine Infusions in Patients with Parkinson's Disease: An Open‐Label Pilot Study - Alexander Khlebtovsky; Israel Steiner; Therese Treves; Ruth Djaldetti (Wiley, 2019)
Amantadine is an antiviral drug available in oral and intravenous forms. Oral amantadine is used to treat the motor symptoms of early Parkinson's disease (PD) and to ameliorate dyskinesia in late‐stage disease. However, the long‐term influence of intravenous amantadine on motor symptoms and dyskinesias in PD has not been investigated. The aim of the present study was to examine the long‐term effect of repeated boosts of intravenous amantadine in patients with PD with and without response fluctuations and dyskinesias. Twelve patients diagnosed with PD, six with levodopa intolerance or insufficient response to antiparkinson medications, and six with response fluctuations and dyskinesias, were treated with intravenous amantadine for 6 months: three sequential infusions over 3 days in the first month followed by five once‐monthly infusions. Changes in motor function and involuntary movements were evaluated with the Unified Parkinson Disease Rating Scale (UPDRS) and Abnormal Involuntary Movement Scale (AIMS; dyskinesia group). A significant immediate improvement in motor scores was documented in both groups after amantadine infusion. However, the difference in mean UPDRS motor score from before the first infusion to after 6 months of treatment was not statistically significant. In patients with dyskinesias, there was a significant improvement in AIMS scores between the first and the last visits (6.3 ± 2.7 vs. 1.6 ± 1.3; P = 0.014). In conclusion, continuous treatment with intravenous amantadine can be useful in patients with PD for immediate relief of motor symptoms and in patients with dyskinesias for progressive reduction of involuntary movements.